The Association between Malnutrition and Pressure Ulcers in Elderly in Long-Term Care Facility - Neloska, Lenche; Damevska, Katerina; Nikolchev, Andjelka; Pavleska, Lidija; Petreska-Zovic, Biljana; Kostov, Milenko (Scientific foundation Spiroski, 2016)
BACKGROUND: Malnutrition is common in elderly and is a risk factor for pressure ulcers. AIM: The aim of the present study was to determine the prevalence of malnutrition in geriatric and palliative patients hospitalised in long-term care facility, and to examine the influence of nutritional status on the prevalence of pressure ulcers (PU). MATERIAL AND METHODS: Descriptive, observational and cross-sectional study including 2099 patients admitted to the Hospital during a 24 month period (January 2013 to December 2014). We recorded: demographic data, body mass index (BMI), Braden score, laboratory parameters of interest (albumin, total protein, RBC count, haemoglobin and iron levels) and presence or absence of malnutrition and pressure ulcers. RESULTS: The pressure ulcer prevalence was 12.9% (256 out of 2099). Based on the BMI classification, 61.7% of patients had a good nutritional status, 27.4% were undernourished, and 2.1% were considered malnourished. Nutritional status was statistically significantly different between patients with and without PU (p < 0.0001). This study also showed that hypoproteinemia, hypoalbuminemia, low RBC was positively associated with PU prevalence. CONCLUSION: The results highlight the impact of nutritional status on the prevalence of pressure ulcers in hospitalised geriatric and palliative population. It is of paramount importance to correctly evaluate the presence of malnutrition in patients at risk of pressure ulcers.
Keywords: geriatric patients; long-term care facility; malnutrition; palliative patients; pressure ulcers